Volatile Constituents of Three Polianthes species Flowers from Viet Nam and Their Inhibitory Activity. Issue 4 (4th July 2017) - Truong, Mai Xuan; Shen, Sida; Ma, Lei; Khang, Pham Van
Abstract: The flowers of Polianthes species were collected in the Thai Nguyen city, Viet Nam. Their volatile oil extracts were obtained via supercritical CO2 extraction and chemical compositions of the volatile oil part were subsequently analysed by GC-FID and GC/MS systems. Some major chemical compositions of volatile oil were identified as methyl 2-amino benzoate, isoeugenol, 1-Eicosene, indole, 5-octadecene, benzylbenzoate, diisobutylphthalate, 1-nonadecene, trans -farnesol. The chemical compositions of volatile oil of Polianthes sessiliflora ( P. sessiliflora ) and Polianthes longiflora ( P. longiflora ) species were being reported for the first time.The activities of total volatile oil extract of the Polianthes genus flowers against HeLa, A459, and Hep-2 cancer cell lines were evaluated.